Search for lepton-flavor-violating τ − → μ − μ + μ − decays at Belle II - The Belle II collaboration; I. Adachi; L. Aggarwal; H. Aihara; N. Akopov; A. Aloisio; N. Althubiti; N. Anh Ky; D. M. Asner; H. Atmacan; V. Aushev; M. Aversano; et al. (Journal of High Energy Physics, 2024)
Abstract We present the result of a search for the charged-lepton-flavor violating decay τ − → μ − μ + μ − using a 424 fb −1 sample of data recorded by the Belle II experiment at the SuperKEKB e + e − collider. The selection of e + e − → τ + τ − events is based on an inclusive reconstruction of the non-signal tau decay, and on a boosted decision tree to suppress background. We observe one signal candidate, which is compatible with the expectation from background processes. We set a 90% confidence level upper limit of 1.9 × 10 −8 on the branching fraction of the τ − → μ − μ + μ − decay, which is the most stringent bound to date.